Upaya Mensukseskan Pemilu 2024: Pendidikan Politik Bagi Pemilih Pemula di Desa Bolali, Wonosari, Klaten - Azizah, Annafi Nurul Ilmi; Sugiyat, Sugiyat; Subando, Joko; Setyaningtyas, Inas; Ridho, Ihsanul Musthofa; Umar, Rohib Mushab (LPMP Imperium, 2024)
The community service activities in this article provide outreach in the form of political education for novice voters which will be held on Saturday, January 27, 2024 at Sutran Hamlet, Bolali, Wonosari, Klaten. With the aim that they will be able to know the importance of using their voting rights and be able to use their rights well and appropriately because one vote is very valuable for the future fate of a country. The methods used in this journal are preparation, implementation and evaluation. The preparation method includes a meeting with the Dukuh Sutan Youth Organization, while the implementation method includes the presentation of material on political education, the evaluation stage in the form of discussion and questions and answers between socialization participants and resource persons. In Indonesia, presidential elections, DPR and DPRD member elections, DPD member elections, and regional head elections will be carried out democratically, this system is known as general elections. The principle of elections is based on the principles of elections that are direct, universal or general, free, secret, honest and fair.